Bronkiektasis: [Bronchiectasis: An Update] - Wahyuni Hariyanto; Helmia Hasan (Jurnal Respirasi, 2016)
Bronchiectasis is characterized by irreversible widening of the medium-sized airways (ectasia), with inflammation, chronic bacterial infection and destruction of the bronchial walls. This could be due to genetic constitusional state or episodic insidental state which not related to intrinsic imunity. The pathogenesis of bronchiectasis is a combination of repeated inflammation and parenchymal fibrotic, lead to bronchial wall weakening and bronchial irreversibly dilatation.“The vicious cycle” and P aeruginosa contributes on progression and severity of disease. The diagnosis of bronchiectasis is made on the basis of high-resolution computed tomography (HRCT) scan findings. Additional testmay be required in spesific clinical setting. Treatment strategies including antibiotic therapy in acute exacerbation and in controlling the microbial growth, therapy according to intrinsic conditional state, therapy to controll the excessive inflammation, promote bronchial hygiene, and consideration of surgery in some cases. In this review, we will describethe etiologies, pathogenesis, diagnostic investigation, and treatment strategies.